Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
E-Adoption and Socio-Economic Impacts 2011
DOI: 10.4018/978-1-60960-597-1.ch002
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Factors Influencing the Adoption of Internet Banking Services in Greece

Abstract: A growing phenomenon in the Internet is the rising exploitation of sophisticated security means (e.g. cryptography, digital signatures etc.) toward the development of novel commerce services for providing electronic transactions, collaborating with business partners or serving customers, regardless of geographical and time limitations. This paper discusses, presents and elaborates on the various factors that affect the adaption of Internet banking services in Greece. In particular, it deals with the factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Extant literature shows evidence of plethora of studies which have used the TAM in the context of the internet banking adoption (Bhattacherjee, 2001;Suh and Han, 2002;Chau and Lai, 2003;Ramayah et al, 2003;Pikkarainen et al, 2004;Eriksson et al, 2005;Lai and Li, 2005;Cheng et al, 2006;McKechnie et al, 2006;Shu-Fong et al, 2007;Hernandez and Mazzon, 2007;Ndubisi, 2007;Yiu et al, 2007;Celik, 2008;Gounaris and Koritos, 2008; 264 JEIM 30,2 Ozdemir et al, 2008;Vatanasombut et al, 2008;Aldás-Manzano et al, 2009;Al-Somali et al, 2009;Hua, 2008;Makris et al, 2009;Polasik and Wisniewski, 2009;Chau and Ngai, 2010;Dimitriadis and Kyrezis, 2010;Featherman et al, 2010;Dimitriadis and Kyrezis, 2011;Gilaninia et al, 2011;Chiou and Shen, 2012;Yousafzai and Yani-de-Soriano, 2012). Bhattacherjee (2001) was the first to use the TAM for the internet banking adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extant literature shows evidence of plethora of studies which have used the TAM in the context of the internet banking adoption (Bhattacherjee, 2001;Suh and Han, 2002;Chau and Lai, 2003;Ramayah et al, 2003;Pikkarainen et al, 2004;Eriksson et al, 2005;Lai and Li, 2005;Cheng et al, 2006;McKechnie et al, 2006;Shu-Fong et al, 2007;Hernandez and Mazzon, 2007;Ndubisi, 2007;Yiu et al, 2007;Celik, 2008;Gounaris and Koritos, 2008; 264 JEIM 30,2 Ozdemir et al, 2008;Vatanasombut et al, 2008;Aldás-Manzano et al, 2009;Al-Somali et al, 2009;Hua, 2008;Makris et al, 2009;Polasik and Wisniewski, 2009;Chau and Ngai, 2010;Dimitriadis and Kyrezis, 2010;Featherman et al, 2010;Dimitriadis and Kyrezis, 2011;Gilaninia et al, 2011;Chiou and Shen, 2012;Yousafzai and Yani-de-Soriano, 2012). Bhattacherjee (2001) was the first to use the TAM for the internet banking adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Online banking is also known as electronic banking and it is an outgrowth of PC banking, which uses the online as the delivery channel to conduct banking activity, for example, transferring funds, paying bills, viewing checking and savings account balances, paying mortgages and purchasing financial instruments and certificates of deposits (Haque et al, 2009). Online banking has been successfully adopted owing to increase in efficiency of services, cost-saving mode or low-cost services, as well as providing advantages of flexible and convenient service delivery (Makris et al, 2009). Gu et al (2009) identified trust as a major enabler to online banking.…”
Section: Introductionmentioning
confidence: 99%